Concept of Fiqh Mu’amalat Between Nahdlatul ‘Ulama and Persatuan Islam: Comparative Study - Imanuddin Abil Fida (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2015)
This article compares the concept of basic thought of Fiqh Mu’amalat by two contemporary religious organization in Indonesia, Nahdlatul ‘Ulama and Persatuan Islam. Both organizations have some disagreement in some issues such as the use of reason in religious interpretations. As a traditionalist movement, the NU holds that the four Madzhab (Sunni school of Islamic law and jurisprudence) provided a reliable and systematic framework therefore no further amendment, and as such Muslims should simply follow and adhere to the ruling of the Madhhab. On the other hand, PERSIS being modernist movement holds that the al-Qur’ān and the al-Sunnah are the only fundamental truths for Muslims and that adherence to Madzhab is not necessary. Therefore, those disagreement has caused a keen debate in their concept of Fiqh Mu’amalat. Despite some those debates, both have some similar thought mainly in concept of usury. To get some understanding about both organizations, the overview of their intellectual development will be elaborated.